2008
DOI: 10.1103/physrevb.77.174405
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical study of a curved planar waveguide with combined Dirichlet and Neumann boundary conditions in a uniform magnetic field

Abstract: A model of a thin straight strip with a uniformly curved section and with different uniform boundary conditions on the opposite edges subjected to the homogeneous magnetic field B is theoretically analyzed within the framework of the linear Schrödinger equation and is applied to the study of the processes in the bent magnetic multilayers and superconducting films. In particular, for the inner Dirichlet and outer Neumann boundaries, it is shown that bend-induced enhancement of the superconductivity survives in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 121 publications
2
11
0
Order By: Relevance
“…The linear dependence of the latter function at large distance between the third particle and the bound pair leads to asymptotic expression (13) for the first-channel function in the expansion (2). On the other hand, the expression ( 13) is consistent with the asymptotic solution of the first-channel equation in (10), in which the long-range terms P 11 (ρ) and −1/(4ρ 2 ) cancel each other at large ρ.…”
Section: General Outline and Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The linear dependence of the latter function at large distance between the third particle and the bound pair leads to asymptotic expression (13) for the first-channel function in the expansion (2). On the other hand, the expression ( 13) is consistent with the asymptotic solution of the first-channel equation in (10), in which the long-range terms P 11 (ρ) and −1/(4ρ 2 ) cancel each other at large ρ.…”
Section: General Outline and Methodssupporting
confidence: 75%
“…Dynamics of few particles confined in low dimensions is of interest in connection with numerous investigations ranging from atoms in ultra-cold gases [1, 2,3,4,5,6,7] to nonostructures [8,9,10]. Experiments with ultra-cold gases in the one-dimensional (1D) and quasi-1D traps have been recently performed [1,11,12,13], amid the rapidly growing interest to the investigation of mixtures of ultra-cold gases [14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was theoretically suggested [16,17,18,19] that an electron moving in a thin curved layer experiences potential energy whose sign and magnitude depend on the local geometric curvature. Such a curvature-induced potential has been observed to cause many intriguing phenomena [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39]: such as bound states of non-interacting electrons in deformed cylinders [40,41,42] and energy band gaps in periodic curved surfaces [43,44,45,46]. Quite recently, surface curvature was found to markedly affect interacting electrons in the quasi-one dimension, resulting in a significant shift in the Tomonaga-Luttinger exponent of thin hollow cylinders subject to periodic surface deformation [47].…”
Section: Introductionmentioning
confidence: 99%
“…We remark that the linearised GL equation (9) which is the main subject of the present study correctly captures the physical phenomena in the uniform magnetic field B and temperature T ranges close to the transition to the normal state when the order parameter Ψ(r) is small and, accordingly, the cubic term in (10) can be safely neglected [31]. The influence of the cubic term can be strongly suppressed also by the choice of the metal or alloy [65] since the GL parameter β contains material-dependent density of states at the Fermi energy N (0), coherence length ξ(0), critical temperature T c and the mean free path l [31]. In addition, it can be shown that equations derived below for the linear case follow also from the complete nonlinear GL theory [52,53].…”
Section: Introductionmentioning
confidence: 60%